Strategi Berkelanjutan Pengendalian Inflasi Pangan di Banjarmasin: Integrasi Pendekatan Internal dan Eksternal - Rahmatullah, Akhsanul (PPJP ULM, 2025)
Food sector inflation significantly impacts economic stability and social welfare, particularly in Banjarmasin City, which heavily relies on external food supplies. Rising food prices directly reduce purchasing power, widen economic inequality, and increase the risk of social instability. This study aims to analyze the factors driving food inflation, evaluate inflation trends over the past five years, and assess the effectiveness of price control policies implemented. Data were obtained from the Central Bureau of Statistics (BPS), Bank Indonesia, and local government policy documents, analyzed using a mixed-methods approach that combines quantitative and qualitative analyses to understand inflation patterns and policy effectiveness. The findings reveal that internal factors such as limited local food production, distribution inefficiencies, and dependency on external supplies largely contribute to price fluctuations. Meanwhile, external factors including disruptions in global supply chains, commodity price volatility, and import policy uncertainties further exacerbate inflationary pressures. Programs such as subsidized market operations, interregional cooperation, development of distribution infrastructure, and price transparency initiatives have been implemented; however, challenges remain regarding supply sustainability and distribution efficiency. Therefore, this study recommends strengthening logistics infrastructure, optimizing supply chains, diversifying local food production, and utilizing agricultural technology to improve productivity and cost efficiency. A sustainability-oriented strategy is expected to maintain food price stability, enhance community welfare, and support regional economic growth.